Bacterial profile and antimicrobial susceptibility patterns among patients clinically suspected of bacterial conjunctivitis at the ophthalmologic clinic of Jimma Medical Center, Southwest Ethiopia - Teklemariam, Eyosias; Damessa, Mekonnen; Nigatu, Mamo; Alemu, Bikila; Tolesa, Kumale; Abdissa, Daba; Fanta, Korinan (Frontiers in Tropical Diseases, 2025)
BackgroundBacterial conjunctivitis is a significant cause of ocular morbidity globally, with increasing antimicrobial resistance posing a challenge to effective treatment. In Ethiopia, data on bacterial profiles and antimicrobial susceptibility patterns in conjunctivitis are limited. This study aimed to assess the bacterial profile and antimicrobial susceptibility patterns among patients clinically suspected of bacterial conjunctivitis at Jimma Medical Center, Ethiopia.MethodsA facility-based cross-sectional study was conducted from January to June 2022. Conjunctival swabs were collected, and bacterial identification and antimicrobial susceptibility testing were performed using standard microbiological methods.ResultsAmong 190 patients, 160 (84.2%) had culture-confirmed bacterial conjunctivitis. Gram-positive bacteria, particularly Coagulase-negative staphylococci (35.6%) and Staphylococcus aureus (21.9%), were predominant. High resistance rates were observed for penicillin, ampicillin, and tetracycline, while meropenem and piperacillin/tazobactam showed better efficacy. Multidrug resistance was detected in 77.5% of isolates.ConclusionsCoagulase-negative staphylococcus and Staphylococcus aureus were the two most predominant bacterial isolates with high resistance to frequently used antibiotics such as penicillin, ampicillin, and tetracycline. Therefore, empirical treatment of bacterial conjunctivitis should be supported by antimicrobial susceptibility tests in the study area.